PENGARUH VALENSI INFORMASI DAN BOBOT INFORMASI PADA BERITA SURVEI ELEKTABILITAS CAPRES TERHADAP KECENDERUNGAN MEMILIH GANJAR PRANOWO SEBAGAI PRESIDEN RI 2024 - Nur Shafira, Hana; Pradekso, Tandiyo; Suryanto Gono, Joyo Nur (Interaksi Online, 2024)
Electability surveys are a trend in politics where they can lead public opinion to certain candidates. From several electability survey news, many of them show that Ganjar's electability tends to decline. This will harm Ganjar in the process of becoming a presidential candidate in the 2024 election, where the news can affect their attitude in voting. This study used an explanatory quantitative research type. The theory used in this study is Integration Information Theory. The results of the hypothesis test showed that there was no effect between the information valence variable (X1) and the information weight variable (X2) on the tendency to elect variable (Y) with a significance value of 0.084 where is more than 0.05.